PENGEMBANGAN MEDIA SMART BOX UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATERI ENERGI KELAS IV SD NEGERI KANGKUNG 3 - Ufera Irba Wiami; Sari Yustiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to develop Smart Box learning media for energy materials and analyze the level of feasibility, practicality and effectiveness in improving learning outcomes in improving students' critical thinking. This research uses the Research and Development (R&D) method with stages including needs analysis, media design, development, expert validation, and trials. The subjects of the study were students with a total of 25 students. The data research instruments used include expert validation sheets, teacher and student questionnaires as well as tests in the form of posttests. The results of the study showed that Smart Box media obtained a validation score of 0.875 with the category "Very Feasible", thus meeting the standards of feasibility of content, presentation, and design of learning media. From the practical aspect, the results of the questionnaire showed that the teacher's response reached 88% and the student's response reached 87.2% which was included in the "Very Practical" category. This shows that the media is easy to use, engaging, and helps the learning process in the classroom. The effectiveness of the media was measured from the postest results which showed that the average student score was 87.60, which had exceeded the Minimum Completeness Criteria (KKM) of 75. The results of the statistical test of one t-test showed that the t-value of 8.9872 was greater than the t-table of 2.0639, so that the results of the study significantly improved students' critical thinking skills in fulfilling the KKM. The percentage of classical completeness reaches 96%, which shows that the media is in the category of very effective. Thus, the Smart Box learning media developed by the researcher is declared feasible, practical and very effective for use in energy materials in Natural Sciences (IPA) class IV subjects and can improve the quality of learning outcomes to improve students' critical thinking skills in elementary school.